2012
DOI: 10.1111/j.1600-0765.2012.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scaling and root planing on interleukin‐1β, interleukin‐8 and MMP‐8 levels in gingival crevicular fluid from chronic periodontitis patients

Abstract: Our observations indicated that short-term nonsurgical therapy resulted in a significant improvement in periodontal indices and in a marked decrease of IL-1β, IL-8 and MMP-8 gingival crevicular fluid levels. Nevertheless, no significant correlations were found between clinical parameters and amounts of humoral factors after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 54 publications
(95 reference statements)
7
68
0
4
Order By: Relevance
“…Hannigan et al reported a significant decrease in soluble ICAM-1 in GCF from patients with chronic periodontitis after SRP [28]. Konopka et al found a marked decrease in IL-1β in GCF at 4 weeks after SRP along with a significant improvement in clinical parameters [23]. At one week after SRP, GCF samples from five patients showed almost the same levels of IL-1β as the baseline, while samples from the other 25 patients showed lower levels than the baseline.…”
Section: Discussionmentioning
confidence: 89%
“…Hannigan et al reported a significant decrease in soluble ICAM-1 in GCF from patients with chronic periodontitis after SRP [28]. Konopka et al found a marked decrease in IL-1β in GCF at 4 weeks after SRP along with a significant improvement in clinical parameters [23]. At one week after SRP, GCF samples from five patients showed almost the same levels of IL-1β as the baseline, while samples from the other 25 patients showed lower levels than the baseline.…”
Section: Discussionmentioning
confidence: 89%
“…IL-1RII expression was also shown to be decreased in stromal and epithelial cells in endometrium specimens obtained from women with endometriosis as compared to healthy subjects [13], while Suzuki et al reported that sIL-1RII was detected with IL-1β in gingival crevicular fluid (GCF) from patients with aggressive (AgP) and chronic periodontitis (CP), though sIL-1RII production in the AgP patients was much lower [14]. It has been reported that many cytokines in GCF are produced from gingival tissue [15] [16]. On the other hand, the IL-1RII producing mechanism in periodontal tissue remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One study collected IL-1β, MMP-8, IL-8 from gingival crevicular fluid in chronic periodontitis subjects [51][52][53] and found that the level decreased after short-term surgical treatment, especially 4 weeks after scaling and root planning. 54 Another study in patients with type 2 diabetes mellitus who had chronic periodontitis reported that nonsurgical periodontal treatment was associated with a reduction in levels of IL, TNF-α and fibrinogen. Moreover, a study showed that periodontal therapy helped to improve glycemic control.…”
Section: Periodontal Treatment and Cerebrovascular Diseasementioning
confidence: 99%